Effect of Rh Addition to Ni/MgO-Al2O3 Catalysts for Dry Reforming of Methane - Ocsachoque, Marco Antonio (2017)
Objective: This study has analyzed the performance of Ni and Ni-Rh catalysts based on MgO/g-Al2O3 in the process of dry reforming of methane (DRM). Methods/Statistical Analysis: The samples were prepared using the incipient wetness impregnation method and were characterized by N2 adsorption, X-ray diffraction (XRD), temperature-programmed reduction (TPR), diffuse reflectance spectroscopy (DRS), surface acidity, X-ray photoelectron spectroscopy (XPS), thermal gravimetric analysis (TGA), and Raman spectroscopy. The catalysts were reduced with hydrogen and measured in the reaction of CH4 with CO2 at two CH4/CO2 ratios. Findings: The 0.5% Rh addition to Ni/MgO-g-Al2O3 improves the activity and the stability for this process. In the bimetallic catalysts, the reduction temperature of the active phase decreases due to the hydrogen spillover mechanism from the noble metal to the catalyst surface, which favors their catalytic activity. On the other hand, the interaction between Rh and the support would be the cause for the better performance of bimetallic catalysts. The Rh-Ni/MgO-g-Al2O3 catalyst is the most active, indicating that the impregnation order affects the catalytic behavior. Improvements/Applications: This study gives promising results for this type of catalyst, also showing the effect of the catalyst preparation on the activity and its relationship with deactivation by coke.